Glacier shrinkage driven by climate change during half a century (1954–2007) in the Ortles-Cevedale group (Stelvio National Park, Lombardy, Italian Alps) - C. D’Agata; D. Maragno; C. Smiraglia; G.A. Diolaiuti; D. Bocchiola (Theoretical and Applied Climatology, 2014)
The recent evolution of a representative subset of Alpine glaciers (i.e. 43 glaciers located in the Ortles-Cevedale group, Stelvio National Park, Italy) is described by analysing surface area changes. The database covers half a century of Alpine glacier history (from 1954 to 2007), thus allowing to describe glacier changes on a relatively long time window. Further, the subset of Alpine glaciers chosen for the analysis are among the best known and studied of Italy, also comprising the widest Italian valley glacier. The analysis provided area surface changes as -19.43 km2 ± 1.2 %, approximately -40 %, from 1954 to 2007. Small glaciers contributed strongly to total area loss. The area change rate accelerated lately, with a surface reduction of approximately 8.7 % between 2003 and 2007, i.e. a mean area loss of approximately 0.693 km2/year. The mean yearly loss over the previous periods (1954-1981, 1981-2003 and 1990-2003) were 0.242, 0.436 and 0.476 km2/year, respectively. From a geodynamical perspective, the Ortles-Cevedale group is now experiencing transition from a glacial system to a paraglacial one. The areas where most recently the main shaping and driving factors were glaciers are now subject to the action of melting water, slope evolution and periglacial processes. We also investigated seasonal values of key climatic variables (1951-2007), namely, temperature, precipitation and snow cover in the area, to evaluate their potential effects upon glacier dynamics. We performed linear regression and Mann-Kendall tests to highlight significant non-stationarity and onset of trends of our target climate variables. We investigated the correlation between local weather variables, North Atlantic Oscillation anomalies and global thermal anomaly to highlight the link of local weather patterns against global weather. We further carried out correlation analysis of weather variables (with different lags) against glacier terminus fluctuations during 1951-2006 for the two most studied glaciers of the Ortles-Cevedale group to ...